Conceptions about the Origin and Evolution of Life by Graduates in Natural Sciences (Research, Society and Development, 2020)
This study was developed at the Federal University of Pampa - Campus Uruguaiana. Moreover, it aimed to identify and analyze the perceptions of students entering the Undergraduate Course in Natural Sciences on the theme Origin and Evolution of Life. Data collection was carried out through a questionnaire. The results were examined qualitatively and quantitatively. After analyzing and discussing the data obtained, we conclude that the representation of university students regarding the theme Origin and Evolution of Life presents elements between religious culture and the scientific approach. There were fragmented answers in relation to the central axis of the question, or inadequate, mixing different theories. Exposing this panorama, the work contributes to the process of training students and provides data to the professors of the course to promote pedagogical strategies aimed at the improvement of teaching processes.